ANALYSIS OF ALLOPURINOL, CUCURBITACIN B, MORINDINE, AND PIPERINE AS XANTHINE OXIDASE INHIBITOR BY MOLECULAR DOCKING - Fitria, Lailatul; Hermawan, Muhammad; Sakti, Sefihara Paramitha (JSMARTech: Journal of Smart Bioprospecting and Technology, 2019)
Xanthine oxidase (XO) is known to be involved in the mechanism of ROS and oxidants production.  XO inhibitor plays role in preventing changes in purines to uric acid so uric acid levels in serum and urine can be reduced. The aim of this study was to analyze the interactions between XO and allopurinol, cucurbitacin B, morindin, or piperine by molecular docking. We obtained XO (1FIQ), allopurinol (CID135401907), cucurbitacin B (CID5281316), morindin (CID151621), and piperine (CID638024) from the database.  Molecular docking was done using Hex 8.0. The docking results were visualized with Discovery Studio 3.5. The interaction of cucurbitacin B with XO and morindin with XO resulted in low docking energy, -375.08 kcal/mol and -377.4 kcal/mol. The docking energy of piperine with XO and allopurinol with XO was -163.32 kcal/mol and -281.4 kcal/mol. Cucurbitacin B and morindin bound to the active site of XO precisely on the FAD domain involving ARG426, ALA338, and ASP360. Both of the compounds established more than 10 bonds of van der waals when interacted with XO. Piperine and allopurinol bound to XO near the Fe2S cofactor. This study suggests that cucurbitacin B and morindin may have high potential as xanthine oxidase inhibitors.Keywords: allopurinol, cucurbitacine B, morindin, piperin, xanthine oxidase